Percutaneous recanalization of totally occluded pulmonary veins after pulmonary vein isolation—intermediate‐term follow‐up. Issue 4 (27th March 2013) - Hill, James; Qureshi, Athar M.; Worley, Sarah; Prieto, Lourdes R.
<x xml:space="preserve">Abstract</x> Objectives Review mid‐term follow‐up of percutaneous intervention for post ablation total pulmonary vein occlusion (PVO). Background Feasibility of percutaneous intervention for PVO has been described, but information remains limited. Methods Patients with total PVO were retrospectively identified from our catheterization database. Medical records, catheterization reports, and outpatient follow‐up were reviewed. Results Between April 2005 and February 2012, 16 patients were identified with a total of 18 PVOs. Symptoms included hemoptysis in 6/16 (46%), cough in 8/16 (50%), chest pain in 8/16 (50%), dyspnea in 13/16 (81%) with mean NYHA Class of 2.6 ± 0.6. Recanalization was accomplished in 14/18 (78%) veins: 11 treated with balloon dilation and 3 with stents. Median follow‐up for 13/14 veins was 13 (0–39) months (one patient with one PVO is awaiting follow‐up). Reocclusion occurred in 7/13 (54%) at mean follow‐up of 3.6 ± 1.6 months (6/10 post‐balloon dilation and 1/3 post‐stenting). Despite reocclusion, the reference vessel diameter increased from 4.8 ± 2.4 to 8.5 ± 4.2 mm (P < 0.001) between the first and second catheterization. Re‐recanalization and stent placement was accomplished in 5/6 (83%), with one reocclusion not attempted. At latest follow‐up 9/13 (69%) recanalized vessels remained patent and percent flow to affected lung quadrant increased from 7.4 ± 3.4% pre‐intervention to 14.3 ± 4.2% (P = 0.004). Mean NYHA Class improved to 1.4 ± 0.4 (P < 0.001). Conclusions Recanalization of total PVO can be accomplished with reasonable mid‐term patency, improved symptoms, and lung perfusion. Reocclusion is common, but vessel growth is often observed allowing placement of a reasonably sized stent at a second intervention. Staged intervention is often necessary to maintain patency. © 2013 Wiley Periodicals, Inc.